The effects of vitamin C supplementation on symptoms of delayed onset muscle soreness - Connolly, D. A. J.; Lauzon, C.; Agnew, J.; Dunn, M.; Reed, B. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The aim of this study was to compare the effects of 8 days of vitamin C (VC) supplementation on elbow flexor delayed onset muscle soreness (DOMS) to 8 days of placebo ingestion. Methods: For 3 days prior to an exercise bout (2¥20 eccentric elbow extensions), and for 5 days after, a treatment group ingested 3¥1 000 mg/day of VC versus 3¥50 mg/day of glucose ingestion for the placebo group over the same time period. All subjects were prescreened via dietary recall to exclude any subjects with habitual VC consumption greater than 400 mg/day. Subject comprised 24 subjects (male and female) randomly divided into 2 groups of 12 subjects. Treatment group comprised 5 females and placebo group comprised 8 females. Results: Data from a repeated measures ANOVA indicate that DOMS was successfully induced in both groups via significant time effects for strength loss (P=0.0001), point tenderness (P=0.0001), elbow flexor decreased range of motion (P=0.013), and subjective pain (P=0.0001). However, there were no significant between group differences in response to any of the aforementioned variables: strength loss (P=0.202), point tenderness (P=0.824), elbow flexor range of motion (P=0.208), subjective pain (P=0.342). Conclusions: The results of this study suggest that a VC supplementation protocol of 3¥1 000 mg/day for 8 days is ineffective in protecting against selected markers of DOMS.